Sinergitas Dinas Sosial dan Yayasan Sayangi Bali dalam Penanganan Anak Terlantar di Kota Denpasar - Dewayanny, Noviana Astrin; Purnamanigsih, Putu Eka; Yasintha, Putu Nomy (CITIZEN CHARTER, 2019)
ABSTRACT Denpasar city is currently trying to protect negilited childern to get the same protection as general children. Therefore, through synergy between Social Service of the Bali Province, Social Service of Denpasar City and Sayangi Bali Foundation are expected to be able to give the best handling for negilited children in the  Denpasar City. This research used descriptive qualitiatif method with data collection techniques1 in the form of observation1, interviews1 and documentation1. This research looks how the synergys between Social Service of the Bali Province, Social Service of Denpasar City and Sayangi Bali Foundation in handling negilited childern in Denpasar City by using Najiyati’s synergy indicators consisting of communication and coordination. The result shows that the synergys it’s been going well based on communication and coordination indicators. But there are still a few things need to be improved, so the synergy can run more optimally.    Keywords : Synergy, Negilited Childern, Child Protection.